Formation and reduction of 3-monochloropropane-1, 2-diol esters in peanut oil during physical refining. (15th May 2016) - Li, Chang; Li, Linyan; Jia, Hanbing; Wang, Yuting; Shen, Mingyue; Nie, Shaoping; Xie, Mingyong
Highlights: Formation of 3-MCPD esters has a positive correlation with MAGs, DAGs and chlorine. Chlorine is more predominant than acylglycerols in terms of precursors. Washing bleached oil can reduce the 3-MCPD esters in deodorized oil. Adding diacetin can mitigate the formation of 3-MCPD esters during deodorizing. Abstract: In the present study, lab-scale physical refining processes were investigated for their effects on the formation of 3-monochloropropane-1, 2-diol (3-MCPD) esters. The potential precursors, partial acylglycerols and chlorines were determined before each refining step. 3-MCPD esters were not detected in degummed and bleached oil when the crude oils were extracted by solvent. While in the hot squeezed crude oils, 3-MCPD esters were detected with low amounts. 3-MCPD esters were generated with maximum values in 1–1.5 h at a certain deodorizing temperature (220–260 °C). Chlorine seemed to be more effective precursor than partial acylglycerol. By washing bleached oil before deodorization with ethanol solution, the precursors were removed partially and the content of 3-MCPD esters decreased to some extent accordingly. Diacetin was found to reduce 3-MCPD esters effectively.